Effects of Cognitive Behavior Therapy on Depression, Illness Perception, and Quality of Life in Atrial Fibrillation Patients - Shan, Qu; Xinxin, Shi; Zhijuan, Xie; Rongjing, Ding; Minjie, Zheng (Frontiers in Psychiatry, 2022)
Background: AF Patients with depression resulted in a markedly reduced quality of life. The purpose of this study was to evaluate the efficacy of cognitive behavior therapy (CBT) on the health-related quality of life (HRQoL). Methods: It was A longitudinal randomised controlled trial with a pre and 12-weeks post-test.90 persons were randomly assigned to either a CBT group(CBT) (n=45) or a treatment as usual (TUA) group (n=45). The outcome were changes in the HRQoL (12-item Short Form Health Survey,SF12, divided into two domains: the physical component summary (PCS) and the mental component summary (MCS)),changes in psychological distress (Hamilton Depression Rating Scale (HAM-D) and Patient Health Questionnaire-9 (PHQ-9)) and Illness Perception (Brief Illness Perception Questionnaire (BIPQ). Results: There were statistically significant differences in score reduction for PHQ-9(t= 3.186, P=0.002), HAMD (t =2.611, P = 0.011), BIPQ (t =7.660，P <0.001), and MCS (t =4.301, P <0.001) between CBT group and TUA group. Conclusions: CBT improved HRQoL, Illness Perception and reduced Depressive symptoms in atrial fibrillation.